A comparison of the susceptibility to pathogenic trypanosoma species of Glossina pallidipes originating from allopatric populations in Kenya - Moloo, S.K.; Zweygarth, E.; Okumu, I.O.; Sabwa, C.L. (OAU/STRC, 1995)
A colony of Glossina pallidipes which originated from Nguruman, Rift Valley Province, Kenya, was significantly more susceptible to infections with stocks of Trypanosoma (Nannomonas) congolense, T. (N) simiae and T. (Trypanozoom) brucei brucei, than a colony of the same species which originated from Shimba Hills, Coast Province, Kenya. Male G. pallidipes from both the colonies were more susceptible to the trypanosome infections than female tsetse. Nevertheless, if the differences in susceptibility of the two G. pallidipes colonies to infections with the above Trypanosoma species reflect transmission of the trypanosomes by the two populations of tsetse in the field, then the epidemiology of trypanosomiasis must differ between these two areas in Kenya. Glossina pallidipes which originated from Nguruman showed higher infection rates to stocks of T. (Duttonella) vivax than that from Shimba Hills. However, the infection rates in the two allopatric populations were high, and ranged from 71.3 to 80.0 percent. Thus, the vector aspects of vivax-trypanosomiasis probably do not differ between these two areas of Kenya.